Innovation of a New Plant Tissue Culture Medium without Utilizing Explosive Chemical Ammonium Nitrate (NH4 NO3) - Hoque, Md. Ekramul; Koly, Mokaram Hanifa; Zarin, Zinat Ara Eakut; Sarker, Chhanda; Sultan, Tipu; Ali, Md. Ershed (Discoveries in Agriculture and Food Sciences, 2025)
The growth and development of explants is governed by the composition of culture medium. Ammonium nitrate (NH4NO3) is a major salt of stock solution-01 for the preparation of Murashige and Skoog (MS 1962) medium. But, it is not available in our country due to many destructive activities. A series of experient was conducted to identified any alternate of ammonium nitrate. The MS (1962) medium and MS powder (Duchefa Biocheme, The Netherland) were used as check treatment-1 and check treatment-2. Two potato varieties viz. Diamant and Asterix were used as experimental materials. Finally, an inorganic salt was indetified as a substitute of ammonium nitrate, which is suitable and excellent performer in the preparation of stock solution-01. The concentrations of the other ingredients of major and minor salt were also modified from the MS 1962 medium. Hence, it is totally different from the MS (1962) medium. The regeneration potentiality of potato onto the new medium was best as compare with the two check treatments. The traits like- node number, leaf number, shoot length, root lengths were highest in new medium. The plantlets were healthy, robust and strong as compare to plantlets regenerated from check treatments-1. The regeneration and plantlet production potentiality of the new tissue culture medium was validated with two other crops viz. Sweet potato and Aloe vera. The new medium showed excellent performance in respect of all the trails under studied in those two crops. Hence, the innovation of the new plant tissue culture medium can be utilized for regeneration and large scale plantlet production of any crops.